Genetic diversity of ex-situ conserved Arabica cofee (Coffea arabica L.) accessions in Ethiopia as revealed by simple sequence repeats markers - Benti, Tadesse; Gebre, Endale; Tesfaye, Kassahun; Berecha, Gezahegn; Lashermes, Philippe; Kyallo, Martina; Yao, Nasser (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2023)
So far, there has been limited use of molecular markers in arabica coffee breeding program in Ethiopia. The objectives of this study were to explore the effectiveness of simple sequence repeats markers (SSRs) in detecting polymor- phism and to assess the extent of genetic diversity and relationships among ex-situconserved Arabica coffee accessions. Sixty-two forest coffee accessions planted in the experimental plot of the Ethiopian coffee breeding program were evaluated using 14 SSR markers. These markers amplified a total of 100 alleles, varying from four to ten alleles per locus, with an average of 7.2 across all loci. The rate of polymorphism ranged from 75 to 100, with a mean value of 96.4 across the accessions. The polymorphic information content (PIC) varied from 0.26 to 0.92, with a mean value of 0.70. The genetic similarity coefficient values between 72% possible pair-wise combinations ranged from 0.18 to 0.50, with overall mean value of 0.44.The unweighted pair group method with arithmetic mean (UPGMA) dendrogram based on Jaccard’s genetic similarity grouped the accessions into five main clusters and two singletons at <0.47 similarity coefficient value. These results indicate the effectiveness of the SSR markers in detecting polymorphism and the presence of a high level of genetic diversity and distant relatedness among the studied coffee accessions. The observed diversity could be exploited in the future coffee breeding program to develop heterotic hybrid coffee varieties through crossing of divergent parental lines. The highly informative SSRs markers can be also used in genetic analysis of Arabica coffee germplasm conserved in the field gene bank at Jimma Agricultural Research Center (JARC) to establish core collections for effective conservation, management and utilization purposes